Do International Study Programmes Pay off for Local Students? - Zhiling Wang; Francesco Pastore; Bas Karreman; Frank van Oort (Institute of Labor Economics (IZA), 2021)
International study programmes are increasing in number worldwide, but little is known about the impact on local students' job prospects, especially in a non-English speaking countries. Using rich administrative data from Statistics Netherlands, we analyse labour market outcomes of native graduates in master programmes of Dutch universities between 2006 to 2014 within 5 years after graduation. A coarsened exact matching analysis within cohort-university-detailed field of study group addresses the self-selection issue by generating a matched sample of students with similar characteristics. We find that graduates from international programmmes obtain a wage premium of 2.3% starting from the 1st year after graduation, ceteris paribus. The wage premium keeps increasing by about 1% every year. We investigate the mechanisms through which the wage premium operates. The wage premia can neither be explained by wage increase via cross-firm mobility, nor by faster upward mobility within a firm. Instead, evidence point towards the differential characteristics of the first job upon graduation. Graduates from international programmes are much more likely to choose large firms that have a higher share of foreign-born employees and have business of trade for the first job. They get a head start in wage level and the initial wage advantages persist in the long-run.
Keywords: I23; J24; F22; 330; international programme; native students; wage premium; coarsened exact matching